Study on Spatial Structure Identification of Urban Agglomeration in Central Yunnan Province Based on Fractal Theory - Yang, Wenzheng; Ma, Jiashen; Pan, Yujun; Li, Meilin (2018 26th International Conference on Geoinformatics, 2018)
This paper took urban agglomeration in the middle of Yunnan Province as a research object, using fractal theory and fractal dimension methods, including aggregation dimension, grid dimension and correlation dimension. ArcGIS and the big data platform of Baidu-Map API were also used to calculate fractal dimension, in order to identify the spatial structure of urban system. There are some findings discovered in this study. Firstly, the density of urban agglomeration in the middle of Yunnan Province is decreasing while taking Kunming as the center. The urban system has a large number of blanks in the coverage of the region, and the potential spatial development of urban agglomeration is huge. Secondly, the capacity dimension is much larger than the information dimension, which shows that the topography of Yunnan High-mountain and Flat-dam restricts the spatial distribution of the urban agglomeration in central Yunnan Province, and the urban agglomeration is still in the primary stage of development. Thirdly, the cow-crow dimension is generally low, showing that the urban agglomeration in central Yunnan Province is limited by natural factors such as topography and water system. The level of traffic correlation needs to be improved. This study provides a reference for the healthy and orderly development of the urban agglomeration in central Yunnan Province, from the degree of aggregation, equilibrium and correlation to identify the spatial structure of urban agglomeration.